Sonification of in-vehicle interface reduces gaze movements under dual-task condition. (September 2015) - Tardieu, Julien; Misdariis, Nicolas; Langlois, Sabine; Gaillard, Pascal; Lemercier, Céline
Abstract: In-car infotainment systems (ICIS) often degrade driving performances since they divert the driver's gaze from the driving scene. Sonification of hierarchical menus (such as those found in most ICIS) is examined in this paper as one possible solution to reduce gaze movements towards the visual display. In a dual-task experiment in the laboratory, 46 participants were requested to prioritize a primary task (a continuous target detection task) and to simultaneously navigate in a realistic mock-up of an ICIS, either sonified or not. Results indicated that sonification significantly increased the time spent looking at the primary task, and significantly decreased the number and the duration of gaze saccades towards the ICIS. In other words, the sonified ICIS could be used nearly exclusively by ear. On the other hand, the reaction times in the primary task were increased in both silent and sonified conditions. This study suggests that sonification of secondary tasks while driving could improve the driver's visual attention of the driving scene. Highlights: We studied the impact of using a sonified or silent interface while performing a visual primary task. We measured participants gaze and performance to both primary and secondary tasks. Participants used the sonified interface nearly exclusively be ear while performing the primary task. The reaction times in the primary task were increased in both sonified and silent conditions.